Detection of Photoperiod Responsive Gene in KDML 105 Rice (Oryza sativa L.) using cDNA-SRAP Technique - Choochai Nettuwakul; Pradit Pongtongkam; Amara Thongpan; Surin Peyachoknagul (Agriculture and Natural Resources, 2007)
Sequence-related amplified polymorphism (SRAP) was used for detecting photoperiod responsive gene of KDML 105 rice (Oryza sativa L.). Ten out of 16 primer combinations gave 42 different bands from the cDNA of KDML 105 rice after exposure to short day (SD) photoperiod. The DNA bands larger than 200 bp were collectively selected for cloning and sequencing. Fourteen from 16 cDNA-SRAP markers showed 87–100% similarity to sequences in the GenBank database, but most nucleotide sequences were unknown genes. Gene expression was further elucidated by RT-PCR. The results, however, were rather contradicted to the obtained cDNA-SRAP pattern. Considering DNA band intensity, there were two candidate genes having higher level of expression in SD treatment. Relative qRT-PCR was used for checking the level of gene expression. The result showed that the expression level of candidate gene from KM2-3 marker increased up to 4.63 folds at 6 days after treatment with SD photoperiod. This indicated its high possibility of being a photoperiod responsive gene which most likely corresponds to another class of gene regulating the flowering time in rice. Cloning of this gene was performed by RT-PCR with a primer pair covering the whole open reading frame (ORF). The 546 bp DNA fragment was cloned, sequenced and analyzed. This fragment had one ORF and deduced a polypeptide of 134 amino acid residues. The nucleotide sequence of this gene was submitted to the GenBank database as gi|83972339.